2018
DOI: 10.1039/c7cp07986a
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of Ag-doped CuS nanocomposites synthesized by a facile polyol method

Abstract: We report the first thermoelectric properties of CuAgS, x = 0-0.75 nanocomposites, synthesized by using a facile polyol method. Systematic characterizations using powder XRD, Rietveld refinement of XRD, EDAX, XPS and Raman spectroscopy confirmed their single phase, hexagonal crystal structure with the space group P6/mmc, nominal elemental composition, valence states of the constituent elements and stoichiometric nature. The TEM images showing the CuS formation of nearly perfect hexagonal disk-like particles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 54 publications
(89 reference statements)
8
51
0
Order By: Relevance
“…Faleev et al [1] proposed metal nanoparticles (NPs) inclusion into semiconducting TE materials can be a useful tool to increase the power factor due to formation of metal-semiconductor interfaces which acts as potential barriers to filter low energy charge carriers. This concept is demonstrated in many reports experimentally [2][3][4]6]. Sumithra et al [2] reported 100 % enhancement in ZT value for Bi 2 Te 3 with 2 vol% Bi nanoinclusins.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Faleev et al [1] proposed metal nanoparticles (NPs) inclusion into semiconducting TE materials can be a useful tool to increase the power factor due to formation of metal-semiconductor interfaces which acts as potential barriers to filter low energy charge carriers. This concept is demonstrated in many reports experimentally [2][3][4]6]. Sumithra et al [2] reported 100 % enhancement in ZT value for Bi 2 Te 3 with 2 vol% Bi nanoinclusins.…”
Section: Introductionmentioning
confidence: 83%
“…This resulting solution with black ppt was washed using steps followed in Ref. 4 for proper removal of DEG. Finally, it was dried at 60 o C in vacuum for 5 hrs to get powder product which was directly used for all characterizations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest zT value of ≈5.45 10 −3 obtained for pure CuS improved slightly to 8.3 × 10 −3 (with S = 11 µV K −1 and k = 1.13 W m −1 K −1 ) at 362 K for one of the doped samples with x = 0.4, and these values were extremely low. An important investigation is made on the effects of Ag doping in CuS by Okram's group . CuS‐ and Ag‐doped CuS samples with composition Cu 1− x Ag x S have been fabricated by a polyol method.…”
Section: Strategies To Improve Thermoelectric Properties Of Copper Sumentioning
confidence: 99%